Mechanical Properties of Rice Straw-Based Paper with Various Adhesives - Bahriani Bahriani; Totok Wianto; Dui Yanto Rahman; sugianto arjo; Sadang Husain (Lambung Mangkurat University Press, 2025)
This study investigates the potential of rice straw, an abundant agricultural byproduct with high cellulose content, as a sustainable raw material for art paper production. The research focuses on the mechanical and physical properties of rice straw-based paper using three adhesives: tapioca starch, corn starch, and polyvinyl acetate (PVAc), across varying compositions. The results reveal that adhesive type and composition significantly influence paper characteristics, including thickness, grammage, density, water absorption, and tensile strength. Tapioca adhesive at a 3:1 ratio yielded the best tensile strength (1.7 × 10⁻² N/m²) and water resistance, outperforming PVAc and corn starch adhesives. These findings highlight the viability of rice straw in creating eco-friendly and high-quality art paper, emphasizing the role of adhesives in optimizing performance. By utilizing rice straw, this study aligns with circular economy principles, reducing agricultural waste and dependency on wood-based pulp while advancing environmentally sustainable paper production.